Mycorrhizae Effect on Growth of Guava Plants (Psidium guajava) Under Nursery Conditions - Padilla-Ramírez, José Saúl; González-Gaona, Ernesto; Osuna-Ceja, Esteban S.; Rodríguez-Moreno, Víctor Manuel; Reyes-Muro, Luis; Sánchez-Lucio, Roberto; Acosta-Díaz, Efrain (European Journal of Applied Sciences, 2026)
Guava (Psidium guajava L.) is the main fruit crop in the Calvillo-Cañones region, with a cultivated area of 6,000 hectares in 2024 and a production of 90,400 tons. Plants for establishing new orchards are obtained primarily through asexual propagation by air layering and cuttings. Both propagation methods use soil as a substrate, and nursery growers do not use products that promote root development to avoid transplant shock. The objective of the present study was to evaluate the effect of mycorrhizae on the development of guava plants. Two experiments were conducted under nursery conditions and the following treatments were evaluated. In Exp.1-2018) 0.0, 3.0, 6.0 and 9.0 g/plant of the mycorrhizae INIFAPMR (Glomus intraradices) and the rooting agent RADIX® 10000 (Indole-3-Butyric acid) at a dose of 2.0 g/plant; whereas in Exp.2-2019) the following treatments were evaluated: 0.0, 3.0, 6.0 and 9.0 g/plant of the mycorrhiza MicorrizaFer (Glomus spp) and the plant growth-promoting bacterium Azospirillum at a dose of 6.0 ml/liter. Guava plants from selection 20, obtained by air layering in 2017 and established in the nursery of the “Los Cañones” Experimental Site of INIFAP, were used. The air layering guava plants were placed under nursery conditions in black plastic pots 15 cm in diameter and 30 cm high, containing composted soil with bovine manure as a substrate. The experimental design was a randomized complete block design with five replications, with one plant as the experimental unit. After 97 and 126 days of applying the treatments in Exp.1 and Exp.2, respectively, the following variables were recorded: plant height (PH), number of leaves (NL), basal stem diameter (BSD), fresh weight of leaves (FWL) and roots (FWR), dry weight of leaves (DWL) and roots (DWR), total dry weight (TDW = DWL + DWR) and the DWL/DWR ratio. Results indicated trends toward greater fresh biomass with Radix® and Azospirillum. However, the DWL/DWR ratio of all mycorrhizal treatments showed lower values ​​than the control without mycorrhizae in Exp. 1, and with treatment Mic. 3.0 g in Exp. 2. These results suggest that there was a greater dry biomass in roots than in the aerial parts, which may contribute to reducing transplant shock and improving establishment of plants in the field.